The importance of drug symbols and halal logos in the pharmaceutical industry: Effect, understanding, and implementation - Ramadan, Hendra; Harbit, Auratul Atifah; Azizah, Siti Nur (Universitas Ahmad Dahlan, 2024)
With its predominantly Muslim population, Indonesia has significant potential in pharmaceuticals and herbal products, making it a focal point for government initiatives to drive growth in the sector. Despite these efforts, compliance with halal standards and obtaining halal certificates still face many challenges. This research examines the efforts to fulfill halal certification obligations by implementing halal standards in pharmaceutical and herbal products. This research uses a descriptive qualitative study; the data was collected through observational reviews and interviews and supplemented with a comprehensive literature study, which includes various sources such as journals, books, online media, and other additional references. This study reveals that setting standards or halal certification involves three parties, namely the Halal Product Assurance Organizing Agency (BPJPH), the Halal Examining Agency (LPH), and the Indonesian Council of Ulama (MUI). BPJPH implements the halal product guarantee. Then BPJPH will submit it to Lembaga Pengkajian Pangan, Obat-obatan dan Kosmetika (LPPOM) as LPH to check the adequacy of documents, compile audits, conduct audits, hold auditor meetings, issue audit memoranda, and submit audit result records to the MUI Halal Fatwa Session. Together with the Fatwa Committee, MUI determines the level of halalness of the product based on the audit results and issues a MUI Halal Decree. Keywords: Herbs, Halal Industry, Halal Certificate, Medicines